Rejection of Isbat for Polygamous Marriage: A Perspective from Critical Legal Studies - Muhammad Muhajir; Akmalia Fitri Mafaza; Sukrin Nurkamiden (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This article examines the rejection of a polygamous marriage legalization request at the West Jakarta Religious Court through Decision Number 1548/Pdt.G/2019/PA.JB, utilizing a critical legal studies perspective. The research is grounded in a multidimensional theoretical framework, incorporating elements of critical legal studies and statutory interpretation to scrutinize the judges’ legal interpretations. Methodologically, the study employs a rigorous approach, combining qualitative analysis of judicial decisions with theoretical insights from legal studies. The findings reveal the judges’ systematic interpretation of relevant legal provisions and highlight the tension between legal certainty, justice, and utility. The theoretical implications suggest a need for legal scholars and practitioners to reexamine prevailing paradigms and consider alternative frameworks that prioritize justice and social utility